Initial Purchase Decision: A Gender Differences Perspective - Eugenius Besli; Maria Helena Chandra; Defitroh Chen Sami'un (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to investigates gender differences in online purchase decision-making by analysing the influence of key factors among men and women. An independent t-test is employed to examine behavioural distinctions, while multiple regression is used to assess the strength of these influencing variables. The findings reveal only slight differences between men and women in their online shopping behaviour. However, the order of influence is consistent across both genders, with store ratings having the strongest impact, followed by live streaming shopping and consumer reviews. Despite the similar order, women are found to be more actively involved in online shopping and show a higher sensitivity to these factors compared to men. These findings highlight gender's influence on consumer behaviour and help businesses refine digital design, marketing, and service strategies to suit each group's preferences.